IFPRI country programs: Lessons from case study successes - Place, Frank; Hazell, Peter B. R. (International Food Policy Research Institute, 2018)
This study was undertaken as part of a larger learning exercise to assess the outcomes and impacts of the International Food Policy Research Institute’s country programs. It reports on in-depth probing of selected successful research contributions to policy outcomes in order to determine if there are any common approaches and actions taken by country program leaders that helped to foster the successes. The selection of case studies was not comprehensive— there were many more identified by country program leaders—nor random, because we desired to have samples from all the countries with country programs. A semi-structured interview approach was followed by the authors and guided by a list of questions (found in Appendix B). The results showed that important factors making successful contributions to policy were building high credibility with local policy makers and donors, having direct access to senior policy makers, partnering with the right people, conducting research on issues over the longer term and not just responding to crises, organizing conferences and meetings around research evidence, and strengthening national capacity for policy research.